Археологічні дослідження Молюхового Бугра - Нераденко, Т.М. (Археологічні дослідження в Україні, 2009)
The results of 2006-2008 archaeological research at the Neolithic and the Copper Age settlement of Molyukhiv Buhor near Novoselytsya village in Chyhyryn Region of Cherkasy Oblast are published.